Xpert (R) MTB/RIF and very low positive detection in bronchoalveolar lavage: diagnostic concerns (2015)
Globally, one in three individuals harbours Myco-bacterium tuberculosis (TB) inside their bodies; thepresence of M. tuberculosis DNA in a person does not mean TB disease.